Gagnagrunnur Framleiðslugagna - Berglind Þórisdóttir 1981-; Frosti Bjarnason 1984-; Ladan Pourvatan 1994- (2017)
Gagnagrunnur framleiðslugagna was our final project for Bachelor of Science/Engineering at Reykjavík University. The project is to design and establish a system of database on a web application for farmed salmon company Stofnfiskur in Iceland. The system designed has been made to keep track of production data from the beginning of the production at the breeding facilities to delivery of the salmon eggs to the customers. The process is trackable within the application from the breeding facilities to the customers and trackable from one breed to another. Various sampling data from different stages of the production process are easily available. There is a centralised database that connects all data about employees, facilities and customers.